PRELIMINARY OBSERVATION ON LIVING HABITS OF ACANTHASTER PLANCI (LINNAEUS) AT PULAU TIKUS, SERIBU ISLANDS - Azis, Aznam; Sukarno, - (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 1977)
During the period of June 1975 to August 1975, observations on living habit and some ecological aspects of Acanthaster planci were made at Pulau Tikus, Seribu Islands. The observations, limited to 8 metres deep, were made at the outer reef located south of Pulau Tikus, covering an area of about 4000 square metres. The density of living stony corals and the damaged caused by the feeding activities of A. planci were also studied. The results show that the average numbers of A. planci per month is 20 individuals per 4000 m2. The sizes of the starfish vary between 26-41 cm in diameter and the number of arms between 10 - 18. The moving distance of the starfish is 0.3 - 8 metres in 24 hours. The stony corals affected are Acropora squamosa (BROOK), A. spathulata (BROOK), A. Latistella (BROOK), A. quelchi (BROOK), Fungia sp.. Montipora ramosa BERNARD, Porites sp., DipIoria sp., and Goniatrea sp.